An evaluation of multiplex bead-based analysis of cytokines and soluble proteins in archived lithium heparin plasma, EDTA plasma and serum samples. (16th November 2016) - Brøndum, Line; Sørensen, Brita Singers; Eriksen, Jesper Grau; Mortensen, Lise Saksø; Lønbro, Simon; Overgaard, Jens; Alsner, Jan
Abstract: Objective: To assess the usability of archived plasma and serum by multiplex (Luminex) analysis of circulating proteins (analytes) by evaluating the day to day variation, the effect of several freeze-thaw cycles, and the influence of the media and choice of anticoagulant. Methods: Nineteen analytes in plasma and serum from 86 head and neck cancer patients and 33 controls were evaluated: EGFR, leptin, OPN, VEGFR-1, VEGFR-2, IL-2, IL-13, PDGF-bb, TNF, PAI-1, SDF-1a, IL-4, IL-6, IL-8, eotaxin, G-CSF, VEGF, GRO-a, and HGF. Results: The correlation between measurements of the same samples analyzed on different dates was reasonable. However, samples run on different dates could exhibit different absolute values. The 75th percentile of the fold differences for samples run on different dates was 2.2. No significant difference was found between one and four freeze-thaw cycles (except for HGF), and the correlation was high. We found significant differences in mean concentrations of the majority of analytes in different media and with different anticoagulants. Only the following analytes did not show difference in mean concentrations: EDTA plasma vs. serum: leptin and VEGFR-2, LH plasma vs. serum: IL-2, IL-13, and VEGF, LH plasma levels vs. EDTA plasma: IL-2 and IL-4. Conclusion: Stored serum, LH plasma, and EDTA plasma from clinical trials can be used for analysis of circulating cytokines and proteins. Variations in measurements occur, but are within reasonable ranges. The optimal type of media depends on the analytes, as different analytes have low number of measurements below the lower limit of quantification and higher dynamic ranges in different media.